Targeting SREBP1 chemosensitizes colorectal cancer cells to gemcitabine by caspase-7 upregulation. Issue 1 (1st January 2019) - Shen, Wenlong; Xu, Ting; Chen, Dong; Tan, Xiaojie
ABSTRACT: Biomarkers for predicting chemotherapy response are important for treatment of colorectal cancer (CRC) patients.SREBP1is involved in cancer cell chemoresistance, but the biological consequences of this activity in CRC are poorly understood. We set up biochemical and cell biology analyzes to analyze SREBP1 expression and chemoresistance. We found that SREBP1 was overexpressed in chemoresistant CRC samples, and that SREBP1 overexpression was correlated with poorer patient survival. Targeting SREBP1 increased chemosensitivity to gemcitabine (Gem) in CRC cells. Additionally, SREBP1 overexpression increased chemoresistance to Gem in CRC cells. SREBP1 overexpression downregulated caspase-7 and decreased CRC cell sensitivity to Gem. Low SREBP1 expression was correlated with high caspase-7 expression in CRC patient samples. Low caspase-7 expression was correlated with poor patient survival. Our findings indicated that upregulation of caspase-7 caused by downregulation of SREBP1 may be a novel prognostic biomarker, and may represent a new therapeutic target in CRC. Graphical abstract: uf0001